Efficacy of late line pertuzumab with trastuzumab and chemotherapy in HER2‐positive metastatic breast cancer: An Australian case series. Issue 6 (19th July 2019) - Bergin, Alice R. T.; Luen, Stephen J.; Savas, Peter; Boolell, Vishal; Cho, Doah; Lynch, Jodi; Nott, Louise; Stuart‐Harris, Robin; Teo, Lee Na; Yap, Saw Yee; Loi, Sherene
Abstract: Background: Pertuzumab, when combined with trastuzumab and chemotherapy, is a highly active human epidermal growth factor receptor 2 (HER2), targeting agent in the neoadjuvant, adjuvant and first‐line metastatic HER2‐positive breast cancer setting. The efficacy of late‐line (after first/second‐line) pertuzumab in combination with trastuzumab and chemotherapy is unknown. Aims: To establish pertuzumab efficacy by performing an audit of patients who received pertuzumab after first‐line HER2 directed therapy. We sought to establish whether efficacy differed by clinicopathological factors. Methods: The primary endpoint was progression‐free survival (PFS) and the secondary endpoint, overall survival (OS). Clinicopathological factors, PFS and OS data were collated and clinicopathological factors associated with PFS were evaluated using Cox regression models. Results: Fourteen women were identified. Six (43%) had hormone receptor (HR) negative and eight (57%) had HR‐positive, metastatic HER2‐positive breast cancer. Median follow up was 22.8 months, median prior lines of therapy were 5 (range: 1–9). Median time from diagnosis of metastatic disease to receiving pertuzumab was 4.5 years (range: 4.2–5.8). All patients received initial chemotherapy with pertuzumab and trastuzumab (taxane‐based 71%). Median PFS was 9 months (95% confidence interval [CI]: 7–not estimable [NE]) and median OS was not reached (95% CI, 16 months–NE). Univariable analysis demonstrated that HR‐negative patients had a significantly longer PFS than HR‐positive patients (hazard ratio = 0.11; 95% CI, 0.01–0.88; P = 0.04). Conclusion: This small cases series reports a favorable PFS and OS for pertuzumab with trastuzumab and chemotherapy in the later line metastatic setting. This finding warrants further study.